Analysis of Heavy Equipment Productivity and Efficiency in Road Construction Projects: A Case Study of JLS Lot 3 Blitar - Silvia, Juniar Megah; Putra, I Nyoman Dita Pahang; Widowati, Elok Dewi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study analyzes the productivity and operational efficiency of heavy equipment in the South Cross Route (JLS) Lot 3 Blitar road construction project. A quantitative descriptive approach was employed using primary data obtained from field observations and time-motion studies, as well as secondary data including project schedules, equipment specifications, and cost data. Equipment productivity was calculated to determine actual execution time and rental costs. The results indicate that earthworks, embankment, aggregate base course, and AC-BC asphalt works achieved higher efficiency than planned, as reflected in shorter execution times and lower operational costs. However, AC-WC asphalt work experienced significant inefficiency due to material supply disruptions and equipment idle time. Productivity imbalance among equipment units was identified as the main factor affecting system performance. This study highlights the importance of synchronizing equipment capacity and ensuring continuous material supply to minimize idle time and improve project efficiency. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and Communities